Understanding selection of antimicrobial resistance in biofilms through experimental evolution. Issue 1 (31st January 2020) - Wickham, Gregory; Trampari, Eleftheria; Webber, Mark
Abstract : Background. Biofilms possess several important properties which differentiate them from free-living cells, including their response to selective pressures. This work demonstrates a link between exposure to non-therapeutic antimicrobials and selection for antibiotic resistance in experimentally evolved biofilms of Pseudomonas aeruginosa . Methods. Biofilms of P. aeruginosa PA14 were experimentally evolved through successive subculture under periodically increasing antimicrobial stress. Beginning at 0.25-times MIC, biofilms were exposed to benzalkonium chloride, ciprofloxacin, colistin, zinc or copper sulfate. When the antimicrobial stress resulted in growth failure, the last successful passage was phenotyped. Biofilm formation was quantified via crystal violet uptake and MICs determined by broth microdilution according to EUCAST guidelines. Results. Experimental evolution selected for mutants which produced approximately four-fold more biomass than the parenteral strain. Both ciprofloxacin and chloramphenicol readily selected for mutants able to survive >1024-times MIC. Conversely, no change in susceptibility was observed for either metal. However, despite zinc sulfate not selecting for decreased susceptibility to itself, cross-resistance to both colistin and meropenem was observed in the zinc-passaged lineages. Benzalkonium chloride did not select for a significant change in susceptibility when grown planktonically. However, when assayed as a biofilm, a 5-fold decrease in benzalkonium chloride susceptibility was observed, indicating a biofilm-specific mechanism of antimicrobial tolerance. Conclusion. Mutants with an increased capacity to form biofilms and decreased antimicrobial susceptibility were successfully selected. Furthermore, zinc sulfate, a common feed additive, was able to select for decreased susceptibility to clinically-relevant antibiotics, lending to concerns that ubiquitous non-therapeutic antimicrobials may act as non-canonical drivers of antibiotic resistance.